2009
DOI: 10.1016/j.devcel.2008.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Displacement of Formins from Growing Barbed Ends by Bud14 Is Critical for Actin Cable Architecture and Function

Abstract: SUMMARY Normal cellular development and function requires tight spatiotemporal control of actin assembly. Formins are potent actin assembly factors that protect the growing ends of filaments from capping proteins. However, it is unresolved how the duration of formin-mediated actin assembly events is controlled, whether formins are actively displaced from growing ends, and how filament length is regulated in vivo. Here, we identify Bud14 as a high affinity inhibitor of the yeast formin Bnr1 that rapidly displac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
100
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(104 citation statements)
references
References 29 publications
3
100
1
Order By: Relevance
“…We previously showed that deletion of BUD14 leads to defects in actin cable architecture and function, with some of the cables in the mother cell appearing abnormally bent or buckled and causing defective secretory vesicle trafficking (13). Our analysis here revealed that kel1⌬ and kel2⌬ mutants each display bud14⌬-like bent cables (Fig.…”
Section: Kel1⌬ and Kel2⌬ Cells Display Actin Cable Defects Similar Tomentioning
confidence: 73%
See 4 more Smart Citations
“…We previously showed that deletion of BUD14 leads to defects in actin cable architecture and function, with some of the cables in the mother cell appearing abnormally bent or buckled and causing defective secretory vesicle trafficking (13). Our analysis here revealed that kel1⌬ and kel2⌬ mutants each display bud14⌬-like bent cables (Fig.…”
Section: Kel1⌬ and Kel2⌬ Cells Display Actin Cable Defects Similar Tomentioning
confidence: 73%
“…Previously, we reported that endogenously tagged GFP-Bud14 localizes to sites of polarized growth, i.e. the bud neck and bud tip/cortex (13). Specifically, GFP-Bud14 was found in multiple puncta enriched at the bud neck and cortex.…”
Section: Bud14 Kel1 and Kel2 Interact To Form A Stable 520-kdamentioning
confidence: 99%
See 3 more Smart Citations